Research on Sealing Assembly and Adjustment Method of Assembled Cabin Door of Space Station. Issue 1 (1st September 2022) - Liu, Shufen; Zhang, Bin; Wang, Tianming; Yi, Zhuoxun; Huang, Ning; Cui, Xiaohang; Zhang, Xun; Yu, Junyu
Abstract: For the new assembled sealed cabin door of space station, its structural characteristics, sealing working principle and sealing assembly and adjustment difficulties are analyzed. The static simulation based on the minimum loading point deformation is studied to obtain the minimum compression ratio boundary. Based on the maximum operating force, the sealing stress calculation and simulation analysis are carried out to obtain the maximum compression rate boundary. It realizes the transformation of multiple open constraints into the compression rate interval, which effectively improves the assembly and adjustment accuracy and efficiency of the assembled cabin door.